TiCoSb-based semi-Heusler single crystal thermoelectric material, preparation method thereof and thermoelectric device

By doping M and R elements in semi-Hasler thermoelectric materials, Ti1-x-yMxRyCoSb single crystals are prepared by metal flux method, the defects and impurities of polycrystalline materials are solved, and efficient thermoelectric performance improvement is achieved and power factor is achieved. And the thermoelectric superiority is significantly improved.

CN119243337AActive Publication Date: 2025-01-03HARBIN INSTITUTE OF TECHNOLOGY (SHENZHEN) (INSTITUTE OF SCIENCE AND TECHNOLOGY INNOVATION HARBIN INSTITUTE OF TECHNOLOGY SHENZHEN)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411202105.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-01-03
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

The existing polycrystalline preparation method of semi-Hasler thermoelectric materials has defects and impurities problems, resulting in uneven and unstable performance, making it difficult to optimize the thermoelectric conversion efficiency, especially the low mobility of TiCoSb materials limits its performance improvement.

Method used

Using the chemical formula of Ti1-x-yMxRyCoSb doped M elements (such as Nb, Ta, Sc, V) and R elements (such as Zr, Hf) to prepare single crystals in a high vacuum environment through metal flux method to control the melt composition and cooling rate, eliminating impurities and defects, improving carrier concentration and phonon scattering point, and improving the power factor and thermal conductivity of the material.

Benefits of technology

A high-performance Ti1-x-yMxRyCoSb single-crystal thermoelectric material was obtained, which significantly improved the thermoelectric conversion efficiency and stability of the material, significantly improved the power factor and thermoelectric superiority, and had better performance than polycrystalline materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243337A_ABST
    Figure CN119243337A_ABST
Patent Text Reader

Abstract

The invention provides a TiCoSb-based semi-Heusler single crystal thermoelectric material. The chemical formula of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti < 1-x-y > M < x > R < y > CoSb, wherein the M element comprises at least one of an Nb element, a Ta element, an Sc element and a V element, the R element comprises at least one of a Zr element and an Hf element, x is not larger than 0.07, and y is not larger than 0.25. According to the TiCoSb-based semi-Heusler single-crystal thermoelectric material, the preparation method and the thermoelectric device provided by the invention, the M element and the alloying R metal element are doped at the Ti position according to the proportion, so that the performance regulation and control of the TiCoSb-based semi-Heusler single-crystal thermoelectric material are realized; the appropriate carrier concentration required by the thermoelectric material is provided through the heterovalent doping effect of M elements in different proportions, so that the power factor PF of the material is improved, and the electrical property of the material is improved; according to the present invention, by introducing the isoelectron alloying effect of the R elements with different proportions, the phonon scattering point location is provided, the thermal conductivity of the material is reduced, and the prepared Ti < 1-x-y > M < x > R < y > CoSb single crystal has good thermoelectric performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thermoelectric materials, and in particular relates to a TiCoSb-based semi-Heusler single crystal thermoelectric material, a preparation method and a thermoelectric device. Background Art

[0002] Thermoelectric power generation is a technology that uses the Seebeck effect to directly convert thermal energy into electrical energy. At present, the Seebeck effect of semiconductor materials has outstanding performance in the field of thermoelectric power generation. The prepared device has the characteristics of small size, no moving parts, compact structure, maintenance-free, noise-free, and high reliability. The semiconductor Seebeck effect has been widely used in deep space exploration and field emergency power supply. In addition, it has broad application prospects and economic benefits in the field of thermoelectric power generation of industrial waste heat and automobile exhaust waste heat recovery.

[0003] One of the important indicators for measuring the thermoelectric conversion efficiency of temperature difference power generation is the structural performance of semiconductor materials. The dimensionless thermoelectric figure of merit zT is usually used to describe the thermoelectric performance of materials, where zT = S 2 σT / κ, where S is the Seebeck coefficient, σ is the electrical conductivity, T is the absolute temperature, and κ is the thermal conductivity. The higher the zT value, the higher the thermoelectric conversion efficiency of the thermoelectric power generation device. Therefore, the ideal thermoelectric material needs to have a high power factor (S 2 However, due to the interrelationship between the thermoelectric parameters (S, σ and κ), it is difficult to optimize these three parameters at the same time, so it is challenging to obtain a high zT value. Among them, optimizing the material mobility can effectively improve the power factor PF of the material without deteriorating the Seebeck coefficient and thermal conductivity, thereby improving the zT value of the material.

[0004] Semi-Heusler materials are a new type of thermoelectric material suitable for medium and high temperature ranges. They have good high-temperature stability, mechanical properties and excellent power factor PF, and the raw materials are relatively cheap, so they have important application and research value. Usually, experiments often use high-purity single metal smelting to synthesize bulk raw materials to prepare semi-Heusler materials, including non-equilibrium synthesis paths such as suspension melting, ball milling and spark plasma sintering to obtain polycrystalline semi-Heusler thermoelectric materials. However, this type of polycrystalline semi-Heusler material often has a large number of defects, which lead to the inhomogeneity and instability of material properties; in addition, there are often a large number of second-phase impurities in polycrystalline materials, which reduce the purity of the material. Including but not limited to the above problems, the theoretical and actual Hall mobility of semi-Heusler thermoelectric materials are quite different, which in turn affects the improvement of the thermoelectric performance of semi-Heusler materials. Although polycrystalline semi-Heusler materials meet the needs of thermoelectric conversion to a certain extent, their performance stability, uniformity and purity still limit their further development and promotion in practical applications.

[0005] At present, the growth of single crystals of semi-Heusler materials mainly adopts the melt growth method and the chemical vapor transport method. The melt growth method requires the preparation of high-purity alloys, which are heated and melted and then injected into a crucible to grow crystals under appropriate conditions. The chemical vapor transport method requires mixing the powders of the required elements, placing them in a quartz tube to establish a temperature gradient, and passing an appropriate carrier gas into the tube to react the elements in the high-temperature area to generate semi-Heusler materials, and finally depositing them in the low-temperature area to form single crystals. Regardless of which method is used, the growth conditions need to be strictly controlled, including parameters such as temperature, pressure, composition, and crystal growth rate. However, the existing preparation methods are usually energy-intensive and complex, so it is difficult to obtain large-sized single crystals of semi-Heusler materials at a low cost and energy consumption.

[0006] TiCoSb materials have attracted extensive attention due to their large Seebeck coefficient and good thermal stability. However, due to the low mobility of polycrystalline TiCoSb materials, there is a large gap between the theoretical and actual power factors (PF), which limits the performance improvement of TiCoSb-based semi-Heusler thermoelectric materials. The current mainstream semi-Heusler single crystal growth method has its inherent shortcomings, which makes the performance optimization of single crystals difficult and complicated. Therefore, the cost and effect of performance optimization of single crystal TiCoSb-based semi-Heusler thermoelectric materials are not ideal. In summary, R&D personnel are urgently needed to make improvements. Summary of the invention

[0007] The purpose of the present invention is to overcome at least one of the above-mentioned deficiencies of the prior art and to provide a TiCoSb-based semi-Heusler single crystal thermoelectric material, a preparation method and a thermoelectric device, which can obtain high-performance Ti 1-x-y M x R y CoSb single crystal thermoelectric material can effectively eliminate impurities and defects inside the crystal during the growth process, thus ensuring the prepared Ti 1-x-y M x R y CoSb single crystal has good thermoelectric properties.

[0008] The technical solution of the present invention is: a TiCoSb-based semi-Heusler single crystal thermoelectric material, wherein the chemical formula of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti 1-x-y M x R y CoSb; wherein the M element includes at least one of the Nb element, the Ta element, the Sc element, and the V element, the R element includes at least one of the Zr element and the Hf element, and x is not greater than 0.07, and y is not greater than 0.25.

[0009] As a further improvement of the technical solution, the chemical formula of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti1-x-y Nb x Hf y CoSb.

[0010] As a further improvement of the technical solution, x=0.04-0.06, y=0.03-0.06.

[0011] The present invention also provides a method for preparing a TiCoSb-based semi-Heusler single crystal thermoelectric material. The method is used to prepare the TiCoSb-based semi-Heusler single crystal thermoelectric material, comprising the steps of:

[0012] Preparation of raw materials, according to the chemical formula Ti 1-x-y M x R y A raw material is prepared by a stoichiometric ratio of CoSb, wherein the M element includes any one of Nb element, Ta element, Sc element, and V element, the R element includes any one of Zr element and Hf element, and x is not greater than 0.07, and y is not greater than 0.25;

[0013] A packaging step, sealing the raw material in a packaging tube under high vacuum;

[0014] A heating step, placing the packaging tube in a heating furnace for heating to melt the raw materials to form a mixed melt;

[0015] In the crystallization step, the heating furnace is cooled at a set rate to obtain Ti 1-x-y M x R y CoSb single crystal thermoelectric material.

[0016] As a further improvement of the technical solution, the step of preparing raw materials further includes adding Sb single metal into the raw materials as a flux; the molar ratio of the flux is 10 to 35 times that of the Ti element.

[0017] As a further improvement of the technical solution, in the heating step, the heating furnace is heated to a set temperature and kept warm for a set time, wherein the set temperature is 1100°C to 1150°C; and the set time is 24h to 72h.

[0018] As a further improvement of the technical solution, the preparation method further includes a centrifugation step after the crystallization step, wherein the flux is thrown out by a centrifuge to obtain Ti 1-x-y M x R y CoSb single crystal thermoelectric material.

[0019] As a further improvement of the technical solution, in the packaging step, air is extracted to achieve a high vacuum sealed environment; the vacuum degree of the high vacuum is less than 1×10-3 ~1×10 -4 Pa.

[0020] As a further improvement of the technical solution, in the heating step, the heating furnace is a pit-type furnace, and the heating rate of the pit-type furnace is 10-15°C / min; in the crystallization step, the cooling rate of the pit-type furnace is 0.1-4°C / h; in the centrifugation step, the centrifugal temperature of the flux is 760°C-900°C.

[0021] The present invention also provides a thermoelectric device, which comprises the TiCoSb-based semi-Heusler single crystal thermoelectric material.

[0022] The present invention provides a TiCoSb-based semi-Heusler single crystal thermoelectric material, wherein the chemical formula of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti 1-x-y M x R y CoSb; wherein the M element includes at least one of Nb, Ta, Sc and V, the R element includes at least one of Zr and Hf, and x is not greater than 0.07, and y is not greater than 0.25. The present invention provides a TiCoSb-based semi-Heusler single crystal thermoelectric material, a preparation method and a thermoelectric device, which achieves performance regulation of the TiCoSb-based semi-Heusler single crystal thermoelectric material by doping M elements and alloying R metal elements in proportion at the Ti position; provides the appropriate carrier concentration required by the thermoelectric material through the alivalent doping effect of M elements in different proportions to increase the power factor PF of the material, thereby improving the electrical properties of the material; provides phonon scattering points by introducing the isoelectronic alloying effect of R elements in different proportions to reduce the thermal conductivity of the material and improve the thermal properties of the material, thereby obtaining a high-performance Ti 1-x- y M x R y CoSb single crystal thermoelectric material can effectively eliminate impurities and defects inside the crystal during its growth process, thus ensuring the prepared Ti 1-x-y M x R y CoSb single crystal has good thermoelectric properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] FIG1( a) is a physical picture of a TiCoSb single crystal in Example 1 of the present invention;

[0025] FIG1( b ) is an X-ray diffraction pattern of a TiCoSb single crystal in Example 1 of the present invention;

[0026] FIG1( c ) is an X-ray diffraction diagram of the orientation of the TiCoSb single crystal in Example 1 of the present invention;

[0027] FIG1( d ) is a TiCoSb single crystal X-ray diffraction-rocking curve test result in Example 1 of the present invention;

[0028] FIG. 2( a ) is a diagram of Ti in Example 2 of the present invention. 1-x Nb x CoSb single crystal resistivity changes with temperature;

[0029] FIG. 2( b ) is a diagram of Ti in Example 2 of the present invention. 1-x Nb x The Seebeck coefficient of CoSb single crystal varies with temperature;

[0030] FIG. 2( c ) is a diagram of Ti in Example 2 of the present invention. 1-x Nb x Mobility diagram of CoSb single crystal and other polycrystalline materials;

[0031] FIG. 2( d ) is a diagram of Ti in Example 2 of the present invention. 1-x Nb x Schematic diagram of the power factor of CoSb single crystal at different temperatures;

[0032] FIG. 2( e ) is a diagram of Ti in Example 2 of the present invention. 1-x Nb x The relationship between the power factor and mobility of CoSb single crystal;

[0033] FIG. 2( f ) is a diagram of Ti in Example 2 of the present invention. 1-x Nb x Comparison of average power factors of CoSb single crystal and other TiCoSb-based polycrystalline materials;

[0034] FIG3( a) is a backscattered electron image of a TiCoSb single crystal in Example 1 of the present invention;

[0035] FIG. 3( b ) is a diagram of Ti in Example 2 of the present invention. 1-x Nb x Backscattered electron image of CoSb single crystal;

[0036] FIG. 3( c ) is a diagram of Ti in Example 6 of the present invention. 1-x Ta x Backscattered electron image of CoSb single crystal;

[0037] FIG. 3( d ) is a diagram of Ti in Example 3 of the present invention. 1-y Hf y Backscattered electron image of CoSb single crystal;

[0038] FIG. 3( e ) is a diagram of Ti in Example 5 of the present invention. 0.89 Nb 0.05 Hf 0.06 Backscattered electron image of CoSb single crystal;

[0039] FIG. 4( a ) is a diagram of Ti in Example 2 of the present invention. 1-x Nb x Total thermal conductivity diagram of CoSb single crystal;

[0040] FIG. 4( b ) is a diagram of Ti in Example 2 of the present invention. 1-x Nb x Electronic thermal conductivity diagram of CoSb single crystal;

[0041] FIG. 4( c ) is a diagram of Ti in Example 2 of the present invention. 1-x Nb x Lattice thermal conductivity diagram of CoSb single crystal;

[0042] FIG. 4( d ) is a diagram of Ti in Example 2 of the present invention. 1-x Nb x Thermoelectric figure of merit of CoSb single crystal;

[0043] FIG. 5( a ) is a diagram of Ti in Example 3 of the present invention. 1-y Hf y Total thermal conductivity diagram of CoSb single crystal;

[0044] FIG. 5( b ) is a diagram of Ti in Example 3 of the present invention. 1-y Hf y Lattice thermal conductivity diagram of CoSb single crystal;

[0045] FIG. 6( a ) is a diagram of Ti in Examples 4 and 5 of the present invention. 1-x-y Nb x Hf y Resistivity of CoSb single crystal varies with temperature;

[0046] FIG. 6( b ) is a diagram of Ti in Examples 4 and 5 of the present invention. 1-x-y Nb x Hf y Seebeck coefficient of CoSb single crystal varies with temperature;

[0047] FIG. 6( c ) is a diagram of Ti in Examples 4 and 5 of the present invention. 1-x-y Nb x Hf y Total thermal conductivity diagram of CoSb single crystal;

[0048] FIG. 6( d ) is a diagram of Ti in Examples 4 and 5 of the present invention. 1-x-y Nb x Hf y Thermoelectric figure of merit of CoSb single crystal;

[0049] FIG. 7( a ) is a diagram of Ti in Example 6 of the present invention. 1-x Ta x Resistivity of CoSb single crystal varies with temperature;

[0050] FIG. 7( b ) is a diagram of Ti in Example 6 of the present invention. 1-x Ta x Seebeck coefficient of CoSb single crystal varies with temperature;

[0051] FIG. 7( c ) is a diagram of Ti in Example 6 of the present invention. 1-x Ta x Total thermal conductivity diagram of CoSb single crystal;

[0052] FIG. 7( d ) is a diagram of Ti in Example 6 of the present invention. 1-x Ta x Thermoelectric figure of merit of CoSb single crystal;

[0053] FIG8(a) is a diagram of Ti in Example 7 of the present invention. 0.98 Sc 0.02 Resistivity diagram of CoSb single crystal at low temperature;

[0054] FIG8(b) is a diagram of Ti in Example 7 of the present invention. 0.98 Sc 0.02 Seebeck coefficient diagram of CoSb single crystal at low temperature;

[0055] FIG8(c) is a diagram of Ti in Example 7 of the present invention. 0.98 Sc 0.02 Power factor diagram of CoSb single crystal at low temperature;

[0056] FIG8(d) is a diagram of Ti in Example 7 of the present invention. 0.98 Sc 0.02 Thermal conductivity diagram of CoSb single crystal at low temperature;

[0057] FIG. 9( a ) is a diagram of Ti in Example 8 of the present invention. 0.97 V 0.03 Resistivity diagram of CoSb single crystal at low temperature;

[0058] FIG. 9( b ) is a diagram of Ti in Example 8 of the present invention. 0.97 V 0.03 Seebeck coefficient diagram of CoSb single crystal at low temperature;

[0059] FIG. 9( c ) is a diagram of Ti in Example 8 of the present invention. 0.97 V 0.03Power factor diagram of CoSb single crystal at low temperature;

[0060] FIG. 9( d ) is a diagram of Ti in Example 8 of the present invention. 0.97 V 0.03 Thermal conductivity diagram of CoSb single crystal at low temperature;

[0061] Fig.10 is Ti in Example 9 of the present invention 1-y Zr y Thermal conductivity diagram of CoSb single crystal at different temperatures;

[0062] FIG. 11( a ) is a diagram of Ti in Example 10 of the present invention. 0.84 Nb 0.06 Hf 0.10 Resistivity diagram of CoSb single crystal;

[0063] FIG. 11( b ) is a diagram of Ti in Example 10 of the present invention. 0.84 Nb 0.06 Hf 0.10 Seebeck coefficient diagram of CoSb single crystal;

[0064] FIG. 11( c ) is a diagram of Ti in Example 10 of the present invention. 0.84 Nb 0.06 Hf 0.10 Power factor diagram of CoSb single crystal;

[0065] FIG. 11( d ) is a diagram of Ti in Example 10 of the present invention. 0.84 Nb 0.06 Hf 0.10 Thermal conductivity diagram of CoSb single crystal. DETAILED DESCRIPTION

[0066] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0067] It should be noted that the terms “setting” and “connection” should be understood in a broad sense. For example, it can be directly setting or connecting, or it can be indirectly setting or connecting through a central component or a central structure.

[0068] In addition, in the embodiments of the present invention, if there are terms indicating orientation or positional relationships such as "longitudinal", "transverse", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., they are based on the orientation or positional relationships or conventional placement states or usage states shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the structure, feature, device or element referred to must have a specific orientation or positional relationship, nor must it be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In the description of the present invention, unless otherwise specified, "multiple" means two or more.

[0069] The various specific technical features and embodiments described in the specific implementation methods can be combined in any suitable manner unless there is any contradiction. For example, different implementation methods can be formed by combining different specific technical features / embodiments. In order to avoid unnecessary repetition, the various possible combinations of the specific technical features / embodiments in the present invention will not be described separately.

[0070] The embodiment of the present invention provides a high-performance TiCoSb-based semi-Heusler single crystal thermoelectric material, wherein the chemical formula of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti 1-x-y M x R y CoSb; wherein the M element includes at least one of Nb, Ta, Sc and V, the R element includes at least one of Zr and Hf, and x is not greater than 0.07, and y is not greater than 0.25. Specifically, the M element can be any one of Nb, Ta, Sc and V, or a mixture of two or more elements, and the R element can be any one of Zr and Hf, or a mixture of two or more elements; through the heterovalent doping of M elements in different proportions, the appropriate carrier concentration required for thermoelectric materials is provided to improve the power factor PF of the material and enhance the electrical properties of the material; through the introduction of the isoelectronic alloying effect of R elements in different proportions, phonon scattering points are provided to reduce the thermal conductivity of the material and enhance the thermal properties of the material, thereby obtaining high-performance Ti 1-x-y M x R y CoSb single crystal thermoelectric material.

[0071] Furthermore, the chemical formula of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti 1-x-y Nb x Hf yCoSb. That is, the M element is Nb element, which provides the appropriate carrier concentration required for the thermoelectric material, and the R element is Hf element. The isoelectronic alloying effect of different proportions of elements introduced by Hf element provides phonon scattering points, which can effectively reduce the thermal conductivity of the material. In this embodiment, x=0.04-0.06, y=0.03-0.06, see the description of Examples 3 to 10 for details.

[0072] An embodiment of the present invention further provides a thermoelectric device, wherein the thermoelectric device comprises the above-mentioned TiCoSb-based semi-Heusler single crystal thermoelectric material.

[0073] The present invention also provides a method for preparing a TiCoSb-based semi-Heusler single crystal thermoelectric material. The method is used to prepare the TiCoSb-based semi-Heusler single crystal thermoelectric material, and comprises the following steps: a raw material preparation step, a packaging step, a heating step, and a crystallization step.

[0074] Preparation of raw materials, according to the chemical formula Ti 1-x-y M x R y The raw material is prepared according to the stoichiometric ratio of CoSb, wherein the M element includes any one of Nb element, Ta element, Sc element, and V element, the R element includes any one of Zr element and Hf element, and x is not greater than 0.07, and y is not greater than 0.25; specifically, single metals Sb, Ti, Co, M and R with a purity of 99.99% are weighed respectively according to the molar ratio as raw materials; wherein the molar ratio of Ti, Co, M and R is 1:1:x:y, and x is not greater than 0.07, and y is not greater than 0.25.

[0075] The packaging step is to seal the raw material in a packaging tube under high vacuum; specifically, after the raw material is placed in the packaging tube, the raw material is sealed inside the packaging tube under high vacuum. Then, a quartz glass plug is sealed inside the packaging tube to maintain the vacuum state inside the packaging tube to prevent oxidation of the raw material, so as to control the melt composition. The high vacuum can be obtained by a mechanical pump or a molecular pump; in this embodiment, the air is extracted by a mechanical pump to achieve a high vacuum sealed environment; the vacuum degree of the high vacuum is less than 1×10 -3 ~1×10 -4 The packaging tube can be an ordinary quartz glass tube, a high-purity quartz glass tube, or an ordinary quartz glass tube with an Al2O3 corundum tube embedded in it.

[0076] A heating step, placing the packaging tube in a heating furnace for heating to melt the raw materials to form a mixed melt;

[0077] In the crystallization step, the heating furnace is cooled at a set rate to obtain Ti 1-x-y M x Ry CoSb single crystal thermoelectric material.

[0078] Furthermore, the step of preparing the raw materials also includes adding Sb single metal to the raw materials as a flux; the molar ratio of the flux is 10 to 35 times that of the Ti element. In this embodiment, the raw materials and the flux (specifically the molar ratio of Ti, Co, and flux) are loaded into an ordinary quartz glass tube at a molar ratio of 1:1:25, and a high vacuum environment is obtained by a mechanical pump to seal the quartz glass plug, so that the melt composition can be controlled. Using Sb single metal as a flux can avoid rapid crystallization caused by supersaturation by controlling the flux ratio, thereby reducing the formation of defects; secondly, because the metal flux Sb has good solubility in target raw materials such as Ti and Co, but poor solubility in other substances that may form impurities. This selective dissolution helps to reduce the crystallization of non-target substances, thereby inhibiting the introduction of impurities. Therefore, Sb raw material is selected as flux, which can suppress impurities and defects in the grown single crystal. The pit furnace is used to start heating and keep warm, so that the raw material is fully melted and evenly melted to become a molten state. In this state, the flux reacts with the material to be grown or forms a melt.

[0079] Furthermore, in the heating step, the heating furnace is heated to a set temperature and kept warm for a set time, wherein the set temperature is 1100°C to 1150°C; the set time is 24h to 72h, so that the mixed melt can form a uniform melt. In this embodiment, the pit furnace is heated to 1100°C at a heating rate of 10°C / min and kept warm for 48h to make the raw materials fully and evenly melted.

[0080] Furthermore, the preparation method further comprises a centrifugation step after the crystallization step, wherein the flux is thrown out by a centrifuge to obtain Ti 1-x-y M x R y CoSb single crystal thermoelectric material. In the centrifugal step, the centrifugal temperature of the flux is 760°C to 900°C, and the excess Sb flux is centrifuged out to finally obtain Ti 1-x-y M x R y CoSb single crystal half-Heusler thermoelectric material.

[0081] Furthermore, in the heating step, the heating furnace is a pit-type furnace, and the heating rate of the pit-type furnace is 10-15°C / min; in the crystallization step, the cooling rate (i.e., cooling rate) of the pit-type furnace is 0.1-4°C / h.

[0082] Specifically, after the raw materials are configured, the pit furnace is heated to 1100°C at a heating rate of 10°C / min and kept warm for 48 hours; after the insulation stage, the pit furnace begins to lower the furnace chamber temperature, Ti1-x-y M x R y CoSb single crystals begin to nucleate and grow. Finally, the flux is centrifuged to obtain the Ti 1-x-y M x R y CoSb single crystal thermoelectric material. The cooling rate of the pit furnace is 0.1-4°C / h. In this embodiment, the pit furnace starts to cool at 2°C / h. During the cooling process, the flux Sb plays a role in suppressing impurities and defects. The temperature is reduced to 760°C-900°C, and the material is taken out and centrifuged for 2 minutes to centrifuge the excess Sb flux, and finally Ti is obtained. 1-x- y M x R y CoSb single crystal semi-Heusler thermoelectric material. Ti prepared by metal flux method 1-x-y M x R y CoSb single crystal semi-Heusler thermoelectric materials have fewer defects and impurities, and their Hall mobility is much higher than the current mainstream polycrystalline TiCoSb-based polycrystalline semi-Heusler thermoelectric materials, so they can achieve a significant improvement in thermoelectric performance.

[0083] The present invention also provides a thermoelectric device, which has the TiCoSb-based semi-Heusler single crystal thermoelectric material in the above embodiment, and thus has very superior thermoelectric performance, great application value and promotion prospects.

[0084] The present invention also provides embodiments 1, 2 and Ti 1-x-y M x R y The embodiments (Example 3 to Example 10) of CoSb semi-Heusler single crystal thermoelectric material and its preparation method are described in detail.

[0085] Example 1

[0086] This example provides a Ti 1-x-y M x R y CoSb semi-Heusler single crystal thermoelectric material and preparation method thereof, wherein x=0, y=0, thus, the chemical composition of the TiCoSb-based semi-Heusler single crystal thermoelectric material is TiCoSb, and the specific steps of the preparation method are as follows:

[0087] 99.99% of metal element is used as raw material, Sb is 15 times of metal flux, and the molar ratio of Ti to Co is 1:1. Sb, Ti and Co are weighed, and the total weight of the raw materials is 60 grams; the weighed raw materials are loaded into an ordinary quartz glass tube, and after being pumped to a high vacuum state by a mechanical pump, a glass plug is sealed at the top 1 / 4 of the glass tube to ensure a high vacuum state inside the quartz glass tube to prevent oxidation of the melt at high temperature, so as to effectively control the melt composition;

[0088] A small corundum crucible is placed at the bottom of the sealed quartz glass tube and placed in the pit furnace near the furnace wall to facilitate obtaining a temperature gradient during the cooling process; the furnace door is closed and the pit furnace heating program is turned on to heat to 1100°C at a heating rate of 10°C / min and keep warm for 48 hours to form a molten uniform melt;

[0089] After the holding time is over, the pit furnace starts to cool down to 800℃ at 2℃ / h. During the process, TiCoSb single crystal nucleates and grows. When the furnace chamber reaches 800℃, the quartz glass tube is taken out of the pit furnace and centrifuged to obtain TiCoSb single crystal thermoelectric material.

[0090] The actual photo of the TiCoSb single crystal block is shown in Figure 1(a). The size of the single crystal block prepared according to the flux ratio can reach 10*10*10mm. 3 About, and the appearance presents a typical pyramid-like shape of semi-Heusler materials; the X-ray diffraction spectrum of the TiCoSb single crystal block is shown in Figure 1(b), and Figure 1(c) shows the directional X-ray diffraction pattern of the TiCoSb single crystal. The space group of the crystal is F-43m, which is consistent with the theoretical space group, and the crystal has a high degree of order; Figure 1(d) is the X-ray diffraction-rocking curve test result, which further proves that the prepared TiCoSb single crystal has high quality, and the half-maximum width (FWHM) of the characteristic peak of the (111) crystal plane is only 0.0150°. As shown in Figure 3(a), the backscattered electron energy spectrum analysis of the bulk material was carried out, and the results showed that the composition of the generated single crystal bulk material is uniform, and there is no segregation of Ti, Co, and Sb. These results show that dense and uniform TiCoSb single crystal thermoelectric materials can be obtained by this method.

[0091] Example 2

[0092] This example provides a TiCoSb-based semi-Heusler single crystal thermoelectric material and a preparation method thereof. The chemical composition of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti 1-x-y M x R y CoSb, where M is Nb, x=0-0.05, y=0, the specific steps are as follows:

[0093] On the basis of preparing high-quality TiCoSb single crystals, Nb elements are doped at the Ti position to increase the carrier concentration of the material, thereby improving the electrical properties of the material. 99.99% of the metal element is used as the raw material, the metal flux Sb is 15 times, the molar ratio of Ti, Co and Nb is 1:1:x, Sb, Ti, Co and Nb are weighed, and the total weight of the raw materials is 60 grams. The subsequent operation is the same as in Example 1, and Ti can be obtained by centrifugation. 1-x Nb x CoSb single crystal thermoelectric material. The prepared Ti 1- x Nb x The backscattered electron spectrum results of CoSb single crystal are shown in Figure 3(b), which shows that the composition of the generated single crystal bulk material is uniform and there is no segregation of Ti, Co, Sb and Nb.

[0094] A series of Ti 1-x Nb x The electrical properties of CoSb (where x = 0-0.043) single crystal samples were tested. As shown in Figure 2 (a) and Figure 2 (b), with the increase of Nb doping content x, the resistivity gradually decreased, and the absolute value of the Seebeck coefficient also gradually decreased, which is consistent with the change trend of electrical properties of doping. As shown in Figure 2 (c), the high-quality Ti prepared in this embodiment 1- x Nb x The mobility of CoSb single crystal is 2 to 3 times that of the same type of polycrystalline material under the same carrier concentration. It can be clearly seen from Figure 2(e) that it is precisely because of the significant improvement in mobility that the power factor PF of the material has greatly increased. As shown in Figure 2(d), the power factor PF of the single crystal prepared in this embodiment is higher than that of the same type of TiCoSb-based polycrystalline material with excellent performance at all temperatures, so the average power factor PF in Figure 2(f) is ave Much higher than the polycrystalline materials of the same system, it can reach ~40μWcm -1 K -2 .

[0095] A series of Ti 1-x Nb x The thermal properties of CoSb (x = 0-0.043) single crystal samples were tested. As shown in Figure 4 (a), Figure 4 (b) and Figure 4 (c), with the increase of Nb doping content, the electronic thermal conductivity κ e gradually increases, while the lattice thermal conductivity κ l The change is not large, but since the electronic thermal conductivity accounts for the total thermal conductivity κ total The proportion of is small, so the total thermal conductivity κ total Ultimately, due to little change in thermal performance and significant improvement in electrical performance, Ti0.995 Nb 0.005 The thermoelectric figure of merit zT of CoSb can reach ~0.46.

[0096] Example 3

[0097] This example provides a TiCoSb-based semi-Heusler single crystal thermoelectric material and a preparation method thereof. The chemical composition of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti 1-x-y M x R y CoSb, R is Hf, where x=0, y=0-0.22, the specific steps are as follows:

[0098] On the basis of preparing high-quality TiCoSb single crystals, Hf element alloying is performed at the Ti position to increase the degree of phonon scattering, reduce the lattice thermal conductivity of the material, and thus improve the thermal performance of the material. 99.99% of the metal element is used as the raw material, the metal flux Sb is 15 times, the molar ratio of Ti, Co and Hf is 1:1:y, Sb, Ti, Co and Hf are weighed, and the total weight of the raw materials is 60 grams. The subsequent operation is the same as in Example 1, and Ti can be obtained by centrifugation. 1-y Hf y CoSb single crystal thermoelectric material. The prepared Ti 1-y Hf y The backscattered electron energy spectrum results of CoSb single crystal are shown in Figure 3(d), which shows that the composition of the generated single crystal bulk material is uniform and there is no segregation of Ti, Co, Sb and Hf.

[0099] Since no doping is performed, the carrier concentration of the material is very low, and it is meaningless to test its conductivity and Seebeck coefficient. 1-y Hf y The electrical properties of CoSb single crystals were tested. 1-y Hf y The thermal conductivity of CoSb single crystal was tested. As shown in Figure 5(a), with the increase of Hf doping content y, the thermal conductivity decreased significantly, which is consistent with the trend of thermal conductivity change of isoelectronic alloying. As can be seen from Figure 5(b), the increase of Hf content leads to a decrease in the total thermal conductivity κ total The decrease is due to the material lattice thermal conductivity κ l The decrease in Hf content indicates that the greater the phonon scattering, the greater the Ti 1-y Hf y The thermal performance of CoSb single crystal is significantly improved. However, if the Hf content is too high, it may scatter electrons strongly, resulting in a significant decrease in the mobility of the material, which is not conducive to improving the performance of the material.

[0100] Example 4

[0101] This example provides a high-performance TiCoSb-based semi-Heusler single crystal thermoelectric material and a preparation method thereof. The chemical composition of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti 1-x-y M x R y CoSb, where M is Nb, R is Hf, where x=0.05, y=0.03, Ti 1-x-y M x R y CoSb to Ti 0.92 Nb 0.05 Hf 0.03 CoSb, the specific steps are as follows:

[0102] On the basis of preparing high-quality TiCoSb single crystals, Nb and Hf elements are doped and alloyed at the Ti position to synergistically improve the electrical and thermal properties of the material. 99.99% of the metal element is used as the raw material, the metal flux Sb is 15 times, the molar ratio of Ti, Co and Hf is 1:1:0.05:0.03, Sb, Ti, Co, Nb and Hf are weighed, and the total weight of the raw materials is 60 grams. The subsequent operation is the same as in Example 1, and Ti can be obtained by centrifugation. 0.92 Nb 0.05 Hf 0.03 CoSb single crystal thermoelectric material. The prepared Ti 0.92 Nb 0.05 Hf 0.03 The backscattered electron energy spectrum results of CoSb single crystal are shown in Figure 3(e), which shows that the composition of the generated single crystal bulk material is uniform and there is no segregation of Ti, Co, Sb, Nb and Hf.

[0103] As shown in Figure 6, by doping and alloying Nb and Hf elements, the electrical and thermal properties of the material are improved in a coordinated manner, the carrier concentration is effectively improved, the phonon scattering degree is increased within a certain range, and Ti 0.92 Nb 0.05 Hf 0.03 The thermoelectric figure of merit zT of CoSb can reach ~0.4.

[0104] Example 5

[0105] This example provides a high-performance TiCoSb-based semi-Heusler single crystal thermoelectric material and a preparation method thereof. The chemical composition of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti 1-x-y M x R y CoSb, where M is Nb, R is Hf, where x=0.05, y=0.06, the specific steps are as follows:

[0106] On the basis of preparing high-quality TiCoSb single crystals, Nb and Hf elements are doped and alloyed at the Ti position to synergistically improve the electrical and thermal properties of the material. 99.99% of the metal element is used as the raw material, the metal flux Sb is 15 times, the molar ratio of Ti, Co and Hf is 1:1:0.05:0.06, Sb, Ti, Co, Nb and Hf are weighed, and the total weight of the raw materials is 60 grams. The subsequent operation is the same as in Example 1, and Ti can be obtained by centrifugation. 0.89 Nb 0.05 Hf 0.06 CoSb single crystal thermoelectric material. The prepared Ti 0.89 Nb 0.05 Hf 0.06 The backscattered electron energy spectrum results of CoSb single crystal are shown in Figure 3(e), which shows that the composition of the generated single crystal bulk material is uniform and there is no segregation of Ti, Co, Sb, Nb and Hf.

[0107] As shown in Figure 6, by doping and alloying Nb and Hf elements, the electrical and thermal properties of the material are improved in a coordinated manner, the carrier concentration is effectively improved, the phonon scattering degree is increased within a certain range, and Ti 0.89 Nb 0.05 Hf 0.06 The thermoelectric figure of merit zT of CoSb single crystal can reach ~0.53.

[0108] Example 6

[0109] This example provides a high-performance TiCoSb-based semi-Heusler single crystal thermoelectric material and a preparation method thereof. The chemical composition of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti 1-x-y M x R y CoSb, where M is Ta, where x = 0 to 0.10, y = 0, the specific steps are as follows:

[0110] On the basis of preparing high-quality TiCoSb single crystal, Ta is doped in the Ti position to increase the carrier concentration of the material. 99.99% of the metal element is used as the raw material, the metal flux Sb is 15 times, the molar ratio of Ti, Co and Ta is 1:1:x, Sb, Ti, Co and Ta are weighed, and the total weight of the raw materials is 60 grams. The subsequent operation is the same as in Example 1, and Ti can be obtained by centrifugation. 1-x Ta x CoSb single crystal thermoelectric material. In this embodiment, x = 0.05, the prepared Ti 0.95 Ta 0.05 The backscattered electron spectrum results of CoSb single crystal are shown in Figure 3(c), which shows that the composition of the generated single crystal bulk material is uniform and there is no segregation of Ti, Co, Sb, and Ta.

[0111] As shown in Figure 7, by doping with Ta elements, the electrical and thermal properties of the material are improved, and the carrier concentration is effectively increased. Due to the existence of mass and stress fluctuations, Ta-doped Ti 1-x Ta x The thermoelectric figure of merit zT of CoSb single crystal thermoelectric material can reach ~0.53.

[0112] Example 7

[0113] This example provides a high-performance TiCoSb-based semi-Heusler single crystal thermoelectric material and a preparation method thereof. The chemical composition of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti 1-x-y M x R y CoSb, where M is Sc, where x = 0.02, y = 0, the specific steps are as follows:

[0114] On the basis of preparing high-quality TiCoSb single crystal, Sc is doped at the Ti position to increase the carrier concentration of the material. 99.99% of the metal element is used as the raw material, the metal flux Sb is 15 times, the molar ratio of Ti, Co and Sc is 1:1:x, Sb, Ti, Co and Sc are weighed, and the total weight of the raw materials is 60 grams. The subsequent operation is the same as in Example 1, and Ti can be obtained by centrifugation. 0.98 Sc 0.02 CoSb single crystal thermoelectric material.

[0115] The low temperature thermoelectric properties of the material are Figure 8(a)-Figure 8(d) As shown, by doping with Sc element, p-type doping of the material is achieved, the carrier concentration is effectively improved, and the electrical performance is improved.

[0116] Example 8

[0117] This example provides a high-performance TiCoSb-based semi-Heusler single crystal thermoelectric material and a preparation method thereof. The chemical composition of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti 1-x-y M x R y CoSb, where M element is V, where x=0.03, y=0, Ti 1-x-y M x R y CoSb to Ti 0.97 V 0.03 CoSb, the specific steps are as follows:

[0118] On the basis of preparing high-quality TiCoSb single crystal, Sc is doped at the Ti position to increase the carrier concentration of the material. 99.99% of the metal element is used as the raw material, the metal flux Sb is 15 times, the molar ratio of Ti, Co and V is 1:1:x, Sb, Ti, Co and V are weighed, and the total weight of the raw materials is 60 grams. The subsequent operation is the same as in Example 1, and Ti can be obtained by centrifugation. 0.97 V 0.03 CoSb single crystal thermoelectric material.

[0119] The low temperature thermoelectric properties of the material are Figure 9(a)-Figure 9(d) As shown, by doping with the V element, p-type doping of the material is also achieved, and the performance is improved.

[0120] Example 9

[0121] This example provides a high-performance TiCoSb-based semi-Heusler single crystal thermoelectric material and a preparation method thereof. The chemical composition of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti 1-x-y M x R y CoSb, where R is Zr, where x=0, y=0-0.20, the specific steps are as follows:

[0122] On the basis of preparing high-quality TiCoSb single crystal, Zr is alloyed separately at the Ti position to improve the scattering point of phonons and increase mass and stress fluctuations. 99.99% of metal single substance is used as raw material, the metal flux Sb is 15 times, the molar ratio of Ti, Co and Zr is 1:1:y, Sb, Ti, Co and Zr are weighed, and the total weight of the raw materials is 60 grams. The subsequent operation is the same as in Example 1, and Ti can be obtained by centrifugation. 1-y Zr y CoSb single crystal thermoelectric material.

[0123] The high temperature thermal conductivity of the material is Fig.10 As shown, through the alloying of Zr element, Zr atoms with large differences in size, mass and vibration characteristics from the matrix atoms are introduced, which affects the mode and rate of heat conduction, resulting in increased phonon scattering and thus reduced thermal conductivity.

[0124] Example 10

[0125] This example provides a high-performance TiCoSb-based semi-Heusler single crystal thermoelectric material and a preparation method thereof. The chemical composition of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti 1-x-y M x R y CoSb, where M is Nb, R is Zr, where x=0.06, y=0.10, the specific steps are as follows:

[0126] On the basis of preparing high-quality TiCoSb single crystals, Nb and Zr elements are doped and alloyed at the Ti position to synergistically improve the electrical and thermal properties of the material. 99.99% of the metal element is used as the raw material, the metal flux Sb is 15 times, the molar ratio of Ti, Co and Hf is 1:1:0.06:0.10, Sb, Ti, Co, Nb and Zr are weighed, and the total weight of the raw materials is 60 grams. The subsequent operation is the same as in Example 1, and Ti can be obtained by centrifugation. 0.84 Nb 0.06 Zr 0.10 CoSb single crystal thermoelectric material.

[0127] Through the doping and alloying of Nb and Zr elements, the electrical and thermal properties of the material are improved synergistically, and the carrier concentration is effectively improved. As shown in Figure 11(d), the phonon scattering distance is greatly increased, so the thermal conductivity in the full temperature range is significantly reduced, and the performance is greatly improved.

[0128] Compared with the prior art, in the above embodiments provided by the present invention, the performance of the TiCoSb-based semi-Heusler single crystal thermoelectric material is controlled by doping M elements and alloying R metal elements in proportion at the Ti position; the suitable carrier concentration required by the thermoelectric material is provided by the alivalent doping effect of M elements in different proportions to improve the power factor PF of the material and the electrical properties of the material; the isoelectronic alloying effect of R elements in different proportions is introduced to provide phonon scattering points to reduce the thermal conductivity of the material and improve the thermal properties of the material, thereby obtaining a high-performance Ti. 1-x-y M x R y CoSb single crystal thermoelectric material.

[0129] Compared with the prior art, the metal flux method is used in the above embodiment of the present invention to achieve Ti 1-x-y M x R y The equilibrium state preparation method of CoSb single crystal uses a high vacuum sealed tube to inhibit oxidation during the melt growth process and control the melt composition; the pit furnace is used for heating and heat preservation to fully melt the raw materials into a molten state. In the molten state, the metal Sb flux reacts with the raw materials or forms a solution; then the pit furnace starts to cool down at a certain cooling rate, and the Ti in the flux is adjusted by adjusting the cooling rate. 1-x-y M x R y CoSb single crystals gradually nucleate and grow; finally, the excess flux is centrifuged to obtain pure Ti 1-x- y M x R yCoSb single crystal thermoelectric material. Metal Sb flux in Ti 1-x-y M x R y During the growth of CoSb single crystal, impurities and defects inside the crystal can be effectively eliminated, thus ensuring the quality of the prepared Ti 1-x-y M x R y Good thermoelectric properties of CoSb single crystal.

[0130] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A TiCoSb-based semi-Heusler single crystal thermoelectric material, characterized in that: The chemical formula of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti 1-x-y M x R y CoSb; wherein the M element includes at least one of the Nb element, the Ta element, the Sc element, and the V element; the R element includes at least one of the Zr element and the Hf element, and x is not greater than 0.07, and y is not greater than 0.

25.

2. The TiCoSb-based semi-Heusler single crystal thermoelectric material according to claim 1, characterized in that: The chemical formula of the TiCoSb-based semi-Heusler single crystal thermoelectric material is Ti 1-x-y Nb x Hf y CoSb.

3. The TiCoSb-based semi-Heusler single crystal thermoelectric material according to claim 2, characterized in that: x=0.04~0.06, y=0.03~0.

06.

4. A method for preparing a TiCoSb-based semi-Heusler single crystal thermoelectric material, characterized in that: The preparation method is used to prepare the TiCoSb-based semi-Heusler single crystal thermoelectric material according to any one of claims 1 to 3, comprising the steps of: Preparation of raw materials, according to the chemical formula Ti 1-x-y M x R y A raw material is prepared by a stoichiometric ratio of CoSb, wherein the M element includes any one of Nb element, Ta element, Sc element, and V element, the R element includes any one of Zr element and Hf element, and x is not greater than 0.07, and y is not greater than 0.25; A packaging step, sealing the raw material in a packaging tube under high vacuum; A heating step, placing the packaging tube in a heating furnace for heating to melt the raw materials to form a mixed melt; In the crystallization step, the heating furnace is cooled at a set rate to obtain Ti 1-x-y M x R y CoSb single crystal thermoelectric material.

5. The preparation method according to claim 1, characterized in that: The step of preparing the raw materials also includes adding Sb single metal into the raw materials as a flux; the molar ratio of the flux is 10 to 35 times that of the Ti element.

6. The preparation method according to claim 5, characterized in that: In the heating step, the heating furnace is heated to a set temperature and kept warm for a set time, wherein the set temperature is 1100° C. to 1150° C. and the set time is 24 h to 72 h.

7. The preparation method according to claim 4, characterized in that: The preparation method further comprises a centrifugation step after the crystallization step, wherein the flux is thrown out by a centrifuge to obtain Ti 1-x-y M x R y CoSb single crystal thermoelectric material.

8. The preparation method according to claim 4, characterized in that: In the packaging step, air is extracted to achieve a high vacuum sealed environment; the vacuum degree of the high vacuum is less than 1×10 -3 ~1×10 -4 Pa.

9. The preparation method according to claim 8, characterized in that: In the heating step, the heating furnace is a pit-type furnace, and the heating rate of the pit-type furnace is 10-15°C / min; In the crystallization step, the temperature reduction rate of the pit furnace is 0.1 to 4°C / h; In the centrifugation step, the centrifugation temperature of the flux is 760°C to 900°C.

10. A thermoelectric device, characterized in that: The thermoelectric device comprises the TiCoSb-based semi-Heusler single crystal thermoelectric material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Low-thermal-conductivity half-Heusler alloy thermoelectric material and preparation method thereof

    CN112018228A

  • Semi-Heusler alloy and preparation method and application thereof

    CN115558832A

  • N-type semi-Heusler alloy thermoelectric material and preparation method thereof

    CN115786794A

  • P-type ZrCoSb-based semi-Heusler single crystal alloy and preparation method thereof

    CN116905091A

  • Adulterated titanium-cobalt-stibium based thermoelectric composite material, and preparation method

    CN1958820A